The endings of specific nomina dedicated to persons should not be emended: nomenclatural issues in Phalangopsidae (Hexapoda: Grylloidea) - Nemésio, André; Dubois, Alain (Zootaxa, 2012)
Costa (2012) intended to “correct” the spellings of the specific epithets of two species of phalangopsid crickets (Grylloidea: Phalangopsidae) described from Brazil in Mews et al. (2009). According to Costa (2012), both specific nomina “were incorrectly formed under the articles of the International Code of Zoological Nomenclature (1999), leading to the need of justified emendations according to the article 33.2.2 of the Code…”.